Development of Conventional Lathe Machine Manual User by Using Augmented Reality Frameworks - Hamid, Abdul; Puan, Loretta Anak; Tamin, Norfauzi; Maslan, Andi; A.S, Darmawan (JOIV : International Journal on Informatics Visualization, 2025)
Machining is one of the familiar subjects in the field of Technical and Vocational Education and Training (TVET) and has been offered at several Vocational Colleges and Institutes of Higher Education (IPT) throughout Malaysia. However, the level of dominance is limited to a handful of students in understanding the learning content and achieving learning outcomes at the end of the course's teaching and learning process. Therefore, this research intends to design and develop a machine manual using an interactive multimedia concept characterized by Augmented Reality (AR). The method of creating forms and developing interactive multimedia routinely uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model as a reference model and guideline for implementing learning. The research instruments used were product development expert review forms and student investigation questionnaires. The research respondents consisted of 80 TVET students from Universiti Tun Hussein Onn Malaysia (UTHM) and Tanjung Piai Vocational School. The data obtained is collected and analyzed periodically using statistical-based software. An evaluation is conducted on the product's design, form, content, and functionality. The results of the analysis on the use of interactive multimedia concepts indicate that the average minimum standard for all variables exceeds 3.25, which is interpreted as Highly Acceptable for the Use of Multimedia-Based Learning. Three experts in the field of multimedia and engineering agree that the product developed has a shape that matches the design and can function effectively. Overall, the research found that the design form, content, and functionality of conventional interactive machines can enhance students' visualization abilities in the teaching and learning process, as well as improve their skills when practicing with the devices.